2006
DOI: 10.1136/sti.2006.020412
|View full text |Cite
|
Sign up to set email alerts
|

Commercial sex venues: a closer look at their impact on the syphilis and HIV epidemics among men who have sex with men

Abstract: Objective: To provide insight into the role of commercial sex venues in the spread of syphilis and HIV among men who have sex with men (MSM). Study: A cross sectional study of 1351 MSM who were diagnosed with early syphilis who did and did not encounter sexual partners at commercial sex venues. Results: Overall, 26% MSM diagnosed with syphilis had sexual encounters at commercial sex venues. Of these, 74% were HIV positive, 94% reported anonymous sex, and 66% did not use a condom. Compared to those who did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…3,29,[36][37][38][39][40][41][42][43][44][45] Multiple studies of MSM in such urban areas have sought to determine whether the venue in which men are meeting their sexual partners has relations with sexual risk behaviors. 38,43,[46][47][48][49][50][51] Additionally, half of the counties in the state in which the study was conducted 52 are classified as rural, with multiple additional counties that have regions also denoted as rural. However, until fiscal year 2007, the city of Indianapolis received no Title I money under the Ryan White CARE Act, a federal initiative that offers assistance to those living with HIV or AIDS.…”
Section: Study Contextmentioning
confidence: 99%
“…3,29,[36][37][38][39][40][41][42][43][44][45] Multiple studies of MSM in such urban areas have sought to determine whether the venue in which men are meeting their sexual partners has relations with sexual risk behaviors. 38,43,[46][47][48][49][50][51] Additionally, half of the counties in the state in which the study was conducted 52 are classified as rural, with multiple additional counties that have regions also denoted as rural. However, until fiscal year 2007, the city of Indianapolis received no Title I money under the Ryan White CARE Act, a federal initiative that offers assistance to those living with HIV or AIDS.…”
Section: Study Contextmentioning
confidence: 99%
“…Leaving home to live with male partner indicates lack of family support as well as other social 19 17 Substance abuse is found to be high among MSM and is associated with multi-partner sex and inconsistent condom use. 25 Consumption of alcohol or any other psychedelic is associated with higher episodes of unprotected anal intercourse and higher rates of condom failure. Also, syndemics of substance abuse contains various social and psychological stressors like psychosocial health problems, depression, and intimate partner violence.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, MSWs who typically solicit clients through an agency (i.e., ''indoor MSW,'' ''call boy'' or ''escort'') appeared to engage in less risky behavior with their commercial sex partners than do street workers [11]. In addition, a number of risk factors for HIV infection among MSWs have been reported in Western countries, including certain risky sexual behaviors with paying or non-paying sexual partners, the location where MSWs meet clients, as well as being sero-positive for syphilis or other sexual transmitted infections [12,13]. However, no venue-related MSWs study has been reported in China.…”
Section: Introductionmentioning
confidence: 95%
“…(2) MSWs acting like call boys in family clubs, a kind of small home-based call boy brothel (FMSW). There were fewer MSWs working in each family club (average 8 MSWs, with a range of [3][4][5][6][7][8][9][10][11][12][13][14][15] and no existing license for entertainment services, but a just an illicit sex trade. (3) Besides the agency-based MSWs, there was a significant proportion of MSWs who were self-employed and found clients by going to public MSM venues like parks (PMSW), thus acting as street MSWs.…”
Section: Introductionmentioning
confidence: 99%